We want to evaluate the sum $$\sum_{L=0}^{\infty}\frac{1}{2}L(L+1)x^L$$

From this set of notes (page 2, equation 8) we find the formula $$\sum_{n=0}^{\infty}\binom{n}{k}y^n = \frac{y^n}{(1-y)^{n+1}}$$ which suggests that I can do $$\frac{1}{x}\sum_{L=0}^{\infty}\binom{L+1}{2}x^{L+1} = \frac{x^L}{(1-x)^{L+2}}\tag{1}\label{eqn1}$$ since $$\frac{1}{2}L(L+1) = \frac{(L+1)!}{2!((L+1)-2)!}$$

But if I do \begin{aligned} \sum_{L=0}^{\infty}\frac{1}{2}L(L+1)x^L & = \sum_{L=0}^{\infty}\frac{L}{2}\frac{d}{dx}x^{L+1} \\ & = \sum_{L=0}^{\infty} \frac{1}{2} \frac{d}{dx} \left[(L+2)x^{L+1} - 2x^{L+1}\right] \\ & = \frac{1}{2} \frac{d^2}{dx^2} \sum_{L=0}^{\infty} x^{L+2} - \frac{d}{dx} \sum_{L=0}^{\infty} x^{L+1} \\ & = \frac{1}{2} \frac{d^2}{dx^2} \frac{x^2}{1-x} - \frac{d}{dx} \frac{x}{1-x} \\ & = \frac{1}{2} \frac{d}{dx} \left[2x(1-x)^{-1} + x^2(1-x)^{-2}\right] - \left[(1-x)^{-1} + x(1-x)^{-2}\right] \\ & = \frac{1}{2} \frac{d}{dx} \frac{2x-x^2}{(1-x)^2} - \frac{1}{(1-x)^2} \\ & = \frac{1}{2} \frac{d}{dx} \left[\frac{x}{(1-x)^2} + \frac{x}{1-x} \right] - \frac{1}{(1-x)^2} \\ & = \frac{1}{2} \left[(1-x)^{-2} + 2x(1-x)^{-3} \right] \\ & = \frac{1+x}{2(1-x)^3} \end{aligned}

which is nowhere close to (1). Where did I go wrong?

All help is welcome.

  • 2
    $\begingroup$ Are you sure the formula to get (1) is right? There seems to be something fishy there. How can a formula summed over n depend on n, if it's going all the way till infinity? $\endgroup$ – Dhanvi Sreenivasan Apr 21 at 10:34
  • $\begingroup$ I'm not entirely sure...that formula came from lecture notes (as linked in the post) for a Math module taught in Arizona University. Wikipedia, on the other hand, on the page "Binomial coefficient" under section 8 "Ordinary generating functions" states instead that the formula is $$\frac{y^k}{(1-y)^{k+1}}$$ but unfortunately does not appear to cite the source. $\endgroup$ – MrABBA Apr 21 at 10:39
  • $\begingroup$ That seems more like it $\endgroup$ – Dhanvi Sreenivasan Apr 21 at 10:50

Note: The cited formula (8) is not correct. There is a typo since we have \begin{align*} \sum_{n=0}^{\infty}\binom{n}{k}y^n = \frac{y^{\color{blue}{k}}}{(1-y)^{\color{blue}{k+1}}}\tag{1} \end{align*} We therefore expect \begin{align*} \frac{1}{x}\sum_{L=0}^{\infty}\binom{L+1}{2}x^{L+1} =\frac{1}{x}\sum_{L=1}^{\infty}\binom{L}{2}x^L = \frac{x^{\color{blue}{1}}}{(1-x)^{\color{blue}{3}}}\tag{2} \end{align*}

Your derivation is fine up to
\begin{align*} \frac{d}{dx}& \frac{2x-x^2}{(1-x)^2} - \frac{1}{(1-x)^2} \\ &=\frac{1}{2}\left((2-2x)(1-x)^{-2}+(2x-x^2)(+2)(1-x)^{-3}\right)-\frac{1}{(1-x)^2}\\ &=\left(\frac{1}{1-x}+\frac{2x-x^2}{(1-x)^3}\right)-\frac{1}{(1-x)^2}\\ &=\frac{1}{(1-x)^3}-\frac{1}{(1-x)^2}\\ &\,\,\color{blue}{=\frac{x}{(1-x)^3}} \end{align*}

in accordance with (2).

Hint: With respect to (1) we have \begin{align*} \frac{y^k}{(1-y)^{k+1}}&=y^k\sum_{n=0}^\infty \binom{-(k+1)}{n}(-y)^n\tag{3}\\ &=\sum_{n=0}^\infty \binom{k+n}{n}y^{n+k}\tag{4}\\ &=\sum_{n=k}^\infty \binom{n}{n-k}y^n=\sum_{n=k}^\infty\binom{n}{k}y^n\tag{5}\\ &=\sum_{n=0}^\infty\binom{n}{k}y^n\tag{6} \end{align*}


  • In (3) we use the binomial series expansion.

  • In (4) we use the binomial identity $\binom{-p}{q}=\binom{p+q-1}{q}(-1)^q$.

  • In (5) we shift the index to start with $n=k$.

  • In (6) we use $\binom{p}{q}=0$ if $q>p$.


In my humble opinion, a simpler way would to consider

$$S=\sum_{L=0}^{\infty}\frac{1}{2}L(L+1)x^L\implies T=2S=\sum_{L=0}^{\infty}L(L+1)x^L$$ $$T=\sum_{L=0}^{\infty}L(L-1+2)x^L=\sum_{L=0}^{\infty}L(L-1)x^L+2\sum_{L=0}^{\infty}Lx^L$$

$$T=x^2\sum_{L=0}^{\infty}L(L-1)x^{L-2}+2x\sum_{L=0}^{\infty}Lx^{L-1}$$ $$T=x^2 \left(\sum_{L=0}^{\infty}x^{L} \right)''+2x \left( \sum_{L=0}^{\infty}x^{L}\right)'$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.